Study Feeding Different Food Types to The Growth and Survival Rate of Nile Fingerlings, Oreochromis niloticus - Pattirane, Chrisoetanto P.; Wahyudi, Dzikri; Sangkia, Frederik Dony; Hapsari, Larasati Putri (Sam Ratulangi University, 2022)
All operations of aquaculture production rely upon the 60% of feed role as an energy source and nutrition for the growth and survival rate of aquatic organisms, especially tilapia fish. This research aims to study feeding different food types to the growth and survival rate of tilapia fingerlings. A sample of fingerlings was derived from the Centre for Aquaculture Production Business Service (BLUPPB) Karawang and reared in Aquaculture Teaching Factory. The fingerlings were stocked with as many as 5 ind/L with three treatments i.e Azolla (P1), artificial feed (P2), and a combination of Azolla and artificial feed (P3). The growth-based length of fingerlings fed by Azolla (P1) is 6 – 7.76 cm, commercial pellet feed (P2) 6 – 11.81 cm, and combination Azolla and commercial pellet feed 6-9.36 cm. The growth-based weight of fingerlings fed by Azolla (P1) is 4 – 5.87 g, commercial pellet feed 4 – 25.11 g, and a combination of Azolla and commercial pellet feed 4 – 11.27 g. The survival rate of fingerlings fed by Azolla is 23%, commercial pellet feed 88%, and combination Azolla and commercial pellet feed 91%.Keywords: Azolla, commercial pellet feed, fingerlings, growth, survival rateAbstrakSeluruh operasional produksi akuakultur sangat bergantung dari 60% peran pakan sebagai sumber nutrisi dan energi bagi pertumbuhan dan tingkat kelangsungan hidup organisme akuatik dalam hal ini ikan nila. Penelitian ini bertujuan untuk melakukan studi terkait pemberian jenis pakan berbeda terhadap pertumbuhan dan tingkat kelangsungan hidup benih ikan nila. Sampel benih ikan nila berasal dari Balai Layanan Usaha Produksi Perikanan Budidaya (BLUPPB) Karawang dan dipelihara di Teachign Factory Budidaya Ikan. Ikan yang dipelihara adalah sebanyak 5 ind/L dengan tiga perlakuan meliputi pakan azolla (P1), pakan pellet komersil (P2) dan kombinasi palat azolla dan pellet komersil (P3). Pertumbuhan panjang ikan yang diberikan perlakuan pakan azolla (P1) adalah 6 - 7.76 cm, pakan pellet komersial (P2) 6 - 11.81 cm dan perlakuan kombinasi pakan pellet komersil dan azolla (P3) 6 - 9.36 cm. Pertumbuhan berat ikan dari perlakuan pakan azolla (P1) 4 – 5.87 g, perlakuan pellet komersial (P2) 4 – 25.11 g dan perlakuan kombinasi pakan pellet komersil dan azolla (P3) 4 – 11.27 g. Tingkat kelangsungan hidup benih ikan nila yang diberikan perlakuan pakan azolla adalah sebesar 23%, pakan pellet komersil 88% dan kombinasi pakan azolla dan pellet komersil adalah 91%.Kata Kunci: azolla, benih, pakan pellet komersil, pertumbuhan, tingkat kelangsungan hidup.